2020
DOI: 10.3390/molecules25030623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lignin Content on Cellulolytic Saccharification of Liquid Hot Water Pretreated Sugarcane Bagasse

Abstract: Lignin contributes to the rigid structure of the plant cell wall and is partially responsible for the recalcitrance of lignocellulosic materials to enzymatic digestion. Overcoming this recalcitrance is one the most critical issues in a sugar-flat form process. This study addresses the effect of low lignin sugarcane bagasse on enzymatic hydrolysis after liquid hot water pretreatment at 190 °C and 20 min (severity factor: 3.95). The hydrolysis of bagasse from a sugarcane line selected for a relatively low lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
(120 reference statements)
3
23
1
Order By: Relevance
“…For LHW pretreatment of oil palm mesocarp fiber, the amount of generated phenolics ranged from 12 to 45 mg/g biomass for pretreatments at 150-220 • C and at severities of 3.25-4.83, thereby exceeding the values found in this study [35]. Even higher values of 55 and 66 mg/g biomass were recently reported for a low and a high lignin variant of LHW pretreated sugar cane bagasse (190 • C, 20 min, log R 0 = 3.95) [36].…”
Section: Phenolicscontrasting
confidence: 78%
“…For LHW pretreatment of oil palm mesocarp fiber, the amount of generated phenolics ranged from 12 to 45 mg/g biomass for pretreatments at 150-220 • C and at severities of 3.25-4.83, thereby exceeding the values found in this study [35]. Even higher values of 55 and 66 mg/g biomass were recently reported for a low and a high lignin variant of LHW pretreated sugar cane bagasse (190 • C, 20 min, log R 0 = 3.95) [36].…”
Section: Phenolicscontrasting
confidence: 78%
“…According to these results, a major proportion of lignin in the pretreated material seemed to be observed since lignin offered a characteristic peak at about 1514 cm −1 , corresponding to the aromatic skeletal vibration, and a higher number of small peaks between 1750 and 1000 cm −1 approximately [73]. This observation could indicate that no depolymerization of lignin during the pretreatment occurred, as already suggested by Ázar et al [77].…”
Section: Content Of Structural Components In Residual Solidssupporting
confidence: 75%
“…Detergent O after pH adjustment of 12 caused maximum lignin removal (Table 2), which in turn showed the higher sugar recovery (50-67%) after enzymatic hydrolysis. Ladeira et al (2020) found 22% lignin in the liquid hot water-pretreated SCB showing 52% of glucose yield after enzymatic hydrolysis. Seo et al (2017) observed 67% lignin removal from lignocellulose after a mixed pretreatment with acids and surfactants.…”
Section: Effect Of Recalcitrant Lignin On Enzymatic Saccharificationmentioning
confidence: 94%